Passive temperature regulation in a heat storage for cooking with internal natural oil circulation - Nydal, Ole Jorgen; Mashingo, Peter; Nylund, Gunn Helen; Bjørshol, Andreas; Olsen, Alexander Peter; Chaciga, Jimmy (Frontiers in Energy Research, 2025)
Energy storage solutions are required for renewable energy systems to provide energy on demand, independently of the time fluctuations of the sources. Electrical batteries provide electrical power, and thermal batteries can likewise provide heating and cooling power directly. An electrical battery can give power at a rated voltage for a partially charged battery as well as for a fully charged battery, and a similar feature would be useful in the case of a thermal battery. In a thermal energy storage system, temperature is a measure of the quality of the energy, and the energy should preferably be available at high temperatures for both partially and fully charged storages. This is the case for latent heat storage systems, as long as the system is in the two-phase region. A similar feature can be achieved in liquid-based sensible heat storage systems where the heat transfer is carried out by the flow of a heat transfer fluid into and out of the storage. If the storage is designed to prevent thermal mixing, either by physical separation of hot and cold fluid in separate containers or by natural thermal stratification in a single container with hot fluid on top of cold fluid, the thermal energy can be extracted at nearly the same temperature as the charging temperature. Then, a temperature control method is needed to feed the storage with a high-temperature stream, independent of the charging power. In this study, we examine a passive thermal regulation approach in a heat storage system designed for cooking applications, utilizing internal natural oil circulation to manage heat distribution and maintain consistent operating temperatures. An expansion-based temperature control method is presented, where the expansion of the heat transfer fluid itself is used as the basis for controlling the charging temperature of an oil-based heat storage unit. A heating element provides the charging power. The oil is heated in a heating chamber that includes a barrier for the circulation of the oil with the storage unit. At a given temperature, the oil expands beyond the barrier, and circulation with the storage unit is initiated. The performance of the method is demonstrated using a set of dedicated experiments, and the method is furthermore applied to heat storage systems for cooking. A strong motivation for the work is to find robust and simple solutions for clean cooking technology in the African environment.